Hybrid method for two parameter singularly perturbed elliptic boundary value problems. Issue 6 (7th December 2021) - Jha, Anuradha; Kadalbajoo, Mohan Krishen
Abstract: In this article, a hybrid scheme for a two‐parameter elliptic problem with regular exponential and boundary layers on Shishkin mesh is analyzed. The hybrid scheme comprises the central difference method in the layer region and the upwind method in the regular part. The use of the central difference in layer region results in a more accurate resolution of layers. The method is shown to have first‐order parameter uniform convergence. The numerical results corroborate the error estimates presented here.